Argatroban for intraoperative anticoagulation in a patient with history of heparin-induced thrombocytopenia and end-stage renal disease undergoing left atrial appendage occlusion: a case report - Eappen, Kevin; Walsh, Kendra L.; Ejiofor, Beverly; Maslow, Andrew; Asher, Shyamal (Frontiers in Medicine, 2025)
Heparin is the standard anticoagulant for structural cardiac procedures, including left atrial appendage occlusion (LAAO). However, alternative agents are needed in patients with contraindications such as heparin-induced thrombocytopenia (HIT). Data on the use of argatroban, a direct thrombin inhibitor, for procedural anticoagulation during LAAO are extremely limited. We describe a 67-year-old man with chronic atrial fibrillation, end-stage renal disease on hemodialysis, and a history of HIT type II who underwent LAAO with a Watchman device under general anesthesia. Due to his renal failure and high risk of recurrent HIT, argatroban was selected for intraoperative anticoagulation. A reduced initial bolus of argatroban achieved supratherapeutic activated clotting time (ACT), and when the infusion was started, ACT levels again exceeded the target range, highlighting the need for close monitoring. The procedure was completed without thromboembolic or hemorrhagic complications. This case demonstrates the effective use of argatroban as an intraoperative anticoagulant in LAAO for patients with HIT and renal impairment. A lower initial bolus and infusion rate may be sufficient with vigilant ACT monitoring to avoid complications of prolonged anticoagulation.